Do the smoking intensity and duration, the years since quitting, the methodological quality and the year of publication of the studies affect the results of the meta-analysis on cigarette smoking and Acute Myeloid Leukemia (AML) in adults?. (March 2016) - Colamesta, Vittoria; D'Aguanno, Silvia; Breccia, Massimo; Bruffa, Sara; Cartoni, Claudio; La Torre, Giuseppe
Highlights: Ever and current smokers present an higher risk compared to never developing AML. There is a growing risk of AML with smoking higher intensity and longer duration. Former smokers have a risk non-significant lower than current. Among long-term quitters (>20 years) there is a significant reduced risk of AML. Abstract: Background: The aim was to perform a systematic review and meta-analysis on the relationship between tobacco smoking and the onset of acute myeloid leukemia (AML) in adults. Methods: PubMed and Scopus databases were systematically searched. In the meta-analysis, random or fixed effects models were used according to the presence of heterogeneity. Study quality was assessed using the Newcastle-Ottawa Scale. Results: Twenty-seven articles were included. Case-control and cohort meta-analyses show that current, ever and former smokers have a significant increased risk to develop AML compared to never smokers [current: OR = 1.36 (1.11–1.66) and RR = 1.52 (1.10–2.14); ever: OR = 1.25 (1.14–1.38) and RR = 1.45 (1.10–1.90); former: OR = 1.21 (1.03–1.41) and RR = 1.45 (1.08–1.94)]. Moreover, increasing smoking intensity and duration is associated with an increase of the risk, OR shift from 1.14 (1–20 pack/years) to 2.36 (>40 pack/years). Discussion and conclusion: Smoking may have a significant role in AML onset in a multistep pathogenesis.